2020
DOI: 10.1371/journal.pone.0242743
|View full text |Cite
|
Sign up to set email alerts
|

High levels of maternal total tri-iodothyronine, and low levels of fetal free L-thyroxine and total tri-iodothyronine, are associated with altered deiodinase expression and activity in placenta with gestational diabetes mellitus

Abstract: Gestational Diabetes Mellitus (GDM) is characterized by abnormal maternal D-glucose metabolism and altered insulin signaling. Dysregulation of thyroid hormones (TH) tri-iodethyronine (T3) and L-thyroxine (T4) Hormones had been associated with GDM, but the physiopathological meaning of these alterations is still unclear. Maternal TH cross the placenta through TH Transporters and their Deiodinases metabolize them to regulate fetal TH levels. Currently, the metabolism of TH in placentas with GDM is unknown, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
(66 reference statements)
0
10
0
2
Order By: Relevance
“…It was found that, in a low selenium diet, increased T4 and T3 concentrations were found, but there was a reduction in DIO2 and DIO3 expression and activity [ 83 ]. In GDM patients, DIO3 levels were increased; however, there was a significant decrease in DIO2 expression and activity in the placenta compared to normal mothers [ 84 ].…”
Section: Placental Selenoproteinsmentioning
confidence: 99%
“…It was found that, in a low selenium diet, increased T4 and T3 concentrations were found, but there was a reduction in DIO2 and DIO3 expression and activity [ 83 ]. In GDM patients, DIO3 levels were increased; however, there was a significant decrease in DIO2 expression and activity in the placenta compared to normal mothers [ 84 ].…”
Section: Placental Selenoproteinsmentioning
confidence: 99%
“…Recent data links a reduction of DIO2 and an increase in DIO3 to the peaked T3 and TSH levels in mothers with gestational diabetes during the third trimester. This is proposed as a response mechanism for ensuring normal levels of fT4 and T3 in the fetus at term (Gutiérrez-Vega et al, 2020). Such changes in DIO2 and DIO3…”
Section: Th Metabolism In the Placentamentioning
confidence: 99%
“…Recent data links a reduction of DIO2 and an increase in DIO3 to the peaked T3 and TSH levels in mothers with gestational diabetes during the third trimester. This is proposed as a response mechanism for ensuring normal levels of fT4 and T3 in the fetus at term (Gutiérrez‐Vega et al, 2020). Such changes in DIO2 and DIO3 activity have already been associated with oxidative stress elicited by hydrogen peroxide in astrocytes, (Lamirand et al, 2008) suggesting a similar regulatory mechanism in the placenta.…”
Section: Th Metabolism In the Placentamentioning
confidence: 99%
“…Placentas from GDM mothers have higher Deiodinase 3 expression and activity, but lower Deiodinase 2 than Normal Glucose Tolerance mothers. [13] According to the literature, hypothyroidism is linked to 6-15 percent of GDM pregnancies. [5,14,15] Additionally, the chance of having GDM is 4.3 times higher in pregnant women who have hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%